Molecular identification of Pseudoplatystoma sp. fish fillets by Multiplex PCR - Cátia Maria de Oliveira Lobo; Fabio Porto-Foresti; Fernanda Dotti do Prado; Renata Torrezan; Ângela Aparecida Lemos de Furtado; Carlos Adam Conte Junior; Eliane Teixeira Mársico (Fundação Oswaldo Cruz (FIOCRUZ), 2014)
Nuclear and mitochondrial genes were used as molecular markers for verifying the iden-tity of fish fillets marketed as pintado (Pseudoplatystoma corruscans). Based on THE polymorphisms of nuclear DNA (RAG2, globin, and EF1 genes) and mitochondrial regions (16S), we examined whether the fillets originated from inbred species of pintado or from hybrids derived from crosses between cachara (P. reticulatum) and pintado. Nuclear genes from both species were detected in the analyzed fillets (n = 29). This clearly iden-tified these fish as interspecific hybrids (or F1/first filial generation) of the type "cacha-pinta," resulting from a cross between female cachara and male pintado. These results demonstrate that monitoring fish fillet trading is crucial for detecting discrepancies between the marketed species and related information declared on the label. Species that are frequently hybridized, such as pintado and cachara, require special attention.